2013
DOI: 10.2478/s13382-013-0103-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between the high risk occupations and bladder cancer in Iran: A case-control study

Abstract: Objectives: The objective of this work was to identify the high-risk occupations in Iran and to re-inspect occupations that were related to bladder cancer. Materials and Methods: In the study, 300 patients suffering from bladder cancer and 500 control individuals were interviewed. Demographic information, occupational history, and history of exposure to chemical compounds such as aromatic amines for each participant were collected. ORs and 95% CIs were calculated using unconditional logistic regression for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
1
14
0
6
Order By: Relevance
“…Khoubi et al introduced exposure to poisons and pesticides as a risk factor for bladder cancer, but in the present study, the history of exposure to pesticides was not significantly correlated with the survival rate of patients with bladder cancer ( p > 0.05) [ 26 ]. We found that most farmers had attended Agricultural Jihad’s training classes and put on personal protective gears during spraying.…”
Section: Discussionmentioning
confidence: 58%
“…Khoubi et al introduced exposure to poisons and pesticides as a risk factor for bladder cancer, but in the present study, the history of exposure to pesticides was not significantly correlated with the survival rate of patients with bladder cancer ( p > 0.05) [ 26 ]. We found that most farmers had attended Agricultural Jihad’s training classes and put on personal protective gears during spraying.…”
Section: Discussionmentioning
confidence: 58%
“…Based on the previous studies, two risk factors, including, hypoactivity[11242528] and occupational exposure[282930] are considered as the specific risk of colorectal and bladder cancers, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show that 20% of bladder cancer are caused by occupational exposure to bladder carcinogens that occur in industrial regions processing paint, dye, metal, pharmaceutical, and petroleum products. [2930] In some developing countries, by controlling occupational exposures to bladder carcinogens, cases of bladder cancer have decreased. [3536]…”
Section: Discussionmentioning
confidence: 99%
“…In total, 20% of the causes of bladder cancer are due to occupational exposure. 34 Based on previous research, the chance of developing BC among bus and heavy drivers is 11.3 (1.3-92.05), in farmers, fisheries, and forestry, it is 6.0 (2.32-15.72), and among metalworkers and welders it is 6.0 (2.84-14.08), these all being higher than others, such as carpenters, at 0.68 (0.35-1.25) ( Table 5).…”
Section: Occupational Exposurementioning
confidence: 99%